2015
DOI: 10.1177/0022022115585874
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Career Decision-Making Profiles Between American and Chinese University Students

Abstract: The current research examined differences in career decision-making profiles (CDMP) between American and Chinese university students, as well as the meditational mechanisms possibly underlying these cultural differences. The results of a survey among American (N = 929) and Chinese (N = 945) undergraduates showed that Chinese participants scored significantly higher on consulting with others, desire to please others, willingness to compromise, dependence on others, procrastination, but lower on aspiration fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 31 publications
3
51
0
Order By: Relevance
“…The participants in the third and fourth samples were undergraduate students at universities in the US and China, who filled out the CDDQ and the CDMP as part of a study in which they were asked to fill out a series of questionnaires in exchange for personal feedback (Guan et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The participants in the third and fourth samples were undergraduate students at universities in the US and China, who filled out the CDDQ and the CDMP as part of a study in which they were asked to fill out a series of questionnaires in exchange for personal feedback (Guan et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, studies have translated, adapted, and tested the validity of the current assessment tools in additional cultures (CDMP; Tian et al, 2014;CDDQ;Creed & Yin, 2006;Mau, 2001) and compared the different patterns of responses among various cultures (CDMP; Guan et al, 2015;CDDQ;Mau, 2004 found that Asian-Americans had greater difficulties then Caucasian-Americans, in both highschool and college samples. Another study by Mau (2001) found that Taiwanese undergraduate students experienced more career decision-making difficulties than American students.…”
Section: Cultural Differences In Career Decision-makingmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that Asian Americans outperformed career decision-making difficulties, and White American perceived the fewest obstacles. Compared to Americans, Guan et al (2015) emphasized that Chinese undergraduates had a better ability in consulting, desire to please others, willingness to compromising, dependence, procrastination, and have lower aspiration for occupation, internal locus of control, and decision making. In light of the Chinese consulting with others, Willner et al (2015) reported that it is used to reduce the CDMD.…”
Section: Introductionmentioning
confidence: 99%